DISC1-mediated dysregulation of adult hippocampal neurogenesis in rats - Lee, Heekyung; Kang, Eunchai; GoodSmith, Douglas; Yoon, Do Yeon; Song, Hongjun; Knierim, James J.; Ming, Guo-li; Christian, Kimberly M. (Frontiers in Systems Neuroscience, 2015)
Adult hippocampal neurogenesis, the constitutive generation of new granule cells in the dentate gyrus of the mature brain, is a robust model of neural development and its dysregulation has been implicated in the pathogenesis of psychiatric and neurological disorders. Previous studies in mice have shown that altered expression of Disrupted-In-Schizophrenia 1 (Disc1), the mouse homolog of a risk gene for major psychiatric disorders, results in several distinct morphological phenotypes during neuronal development. Although there are advantages to using rats over mice for neurophysiological studies, genetic manipulations have not been widely utilized in rat models. Here, we used a retroviral-mediated approach to knockdown DISC1 expression in dividing cells in the rat dentate gyrus and characterized the morphological development of adult-born granule neurons. Consistent with earlier findings in mice, we show that DISC1 knockdown in adult-born dentate granule cells in rats resulted in accelerated dendritic growth, somatic hypertrophy, ectopic dendrites, and mispositioning of new granule cells due to overextended migration. Our study thus demonstrates that the Disc1 genetic manipulation approach used in prior mouse studies is feasible in rats and that there is a conserved biological function of this gene across species. Extending gene-based studies of adult hippocampal neurogenesis from mice to rats will allow for the development of additional models that may be more amenable to behavioral and in vivo electrophysiological investigations. These models, in turn, can generate additional insight into the systems-level mechanisms of how risk genes for complex psychiatric disorders may impact adult neurogenesis and hippocampal function.